1992
DOI: 10.1002/hed.2880140305
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam therapy for skin cancer of the head and neck

Abstract: We retrospectively analyzed 99 patients with 115 sites of skin cancer, predominantly involving the head and neck, treated with electron beam therapy. Our objective was to determine the local control rate, radiotherapy reactions, cosmesis, and salvage treatment. Forty-three percent of patients received radiotherapy after biopsy, 41% were treated for recurrence following other modalities of treatment, and 16% had positive margins after surgical excision. With minimum and mean follow-up of 24 and 47 months, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 4 publications
2
12
0
1
Order By: Relevance
“…According to Lovett et al, newly diagnosed squamous cell skin cancer was locally controlled in 87% of cases (recurrent tumors in 65%) [9]. Comparable results were reported by other groups [10,11]. FDG-PET has been used for response monitoring in both lung and esophageal cancer.…”
Section: Discussionsupporting
confidence: 59%
“…According to Lovett et al, newly diagnosed squamous cell skin cancer was locally controlled in 87% of cases (recurrent tumors in 65%) [9]. Comparable results were reported by other groups [10,11]. FDG-PET has been used for response monitoring in both lung and esophageal cancer.…”
Section: Discussionsupporting
confidence: 59%
“…1 The skin of the head and neck is a common site for the development of cutaneous cancer, 2 and both SCC and malignant melanoma pose a particular therapeutic challenge because of their potential for metastatic spread. Overall, approximately 5% of cutaneous SCCs spread to regional lymph nodes, whereas the metastatic rate for cutaneous melanoma is approximately 20%.…”
mentioning
confidence: 99%
“…Despite the inferior local control rate associated with EBRT on multivariate analysis reported by Lovett et al [32], several other series reported favorable outcomes with local control rate comparable with superficial x-ray treatments, ranging from 81 to 95% [29,[40][41][42][43]. Furthermore, these studies reported good cosmetic outcomes in contrast to those reported by Lovett et al [32].…”
Section: Electron Beam Radiotherapymentioning
confidence: 79%
“…The ability to deliver a uniform radiation dose to a few centimeter depth of human tissue with a steep dose fall beyond the therapy range makes the electron beam suitable for superficial cancer treatments [39], including skin cancer in the H/N region [40]. The energies used for electron beam radiotherapy (EBRT) vary from 4 to 20 MeV, resulting in an effective treatment depth of 2-6 cm.…”
Section: Electron Beam Radiotherapymentioning
confidence: 99%